Efficiency of airline industry amid market shocks: Evidence from Indian market - Dhaliwal, Poonam; Mavi, Anupreet Kaur; Sharma, Nishi (Asian Journal of Economic Modelling, 2025)
The airline industry plays a vital role in the economy, but recently, it has encountered challenges leading to financial instability and even the permanent closure of several well-established airlines. The failure of airline companies creates ripple effects; therefore, it is imperative to measure their efficiency. The present paper analyzes the efficiency of the Indian airline industry from 2003 to 2023 and investigates the impact of the global financial crisis, demonetization, and COVID-19 on efficiency. The results of the Mann-Whitney test proclaim the significant negative impact of demonetization on low-cost carriers and the overall industry. However, full-service carriers are discerned not to be significantly affected by demonetization because they mostly have corporate bookings that use banking channels to transfer funds. The financial crisis and COVID-19 have a profound impact on the efficiency of airlines. The results reveal that efficiency decreased after COVID-19 due to stringent travel restrictions and lockdowns. It is observed that Indian airlines are not operating at an optimal scale of operation, highlighting the need to function in consonance with market demand. The full-service carriers need to diversify their offerings for sustainability. The results are expected to be highly fruitful for the global airline industry, market regulators, and policymakers.